Visualized experimental investigation on cross-flow indirect evaporative cooler with condensation. (25th December 2018) - Meng, Dandong; Lv, Jian; Chen, Yi; Li, Han; Ma, Xuejian
Highlights: A visualized cross-flow IEC is constructed. Two turning points are determined. Five performance is analysed under three states. The thermal resistance is non-ignorable due to condensation. Abstract: In hot and humid regions, condensation will easily occur in the dry channels of indirect evaporative cooler (IEC) due to high dew point temperature of primary air. However, the visualized investigation on cross-flow IEC with condensation has seldom been reported by previous studies. Therefore, a visualized cross-flow IEC was constructed with a transparent cover plate for observing the condensation in a primary air channels. A series of experiment had been carried out to investigate the comprehensive performance of IEC under different inlet primary air temperature and humidity. The outlet primary air temperature, wb-effectiveness, water consumption rate, heat transfer rate and condensation rate were analysed in detail under non-condensation, partial condensation and total condensation cases. The experimental results showed that the turning point from non-condensation to partial condensation was 33.0 °C under relative humidity of 50%, 29.0 °C under relative humidity of 60% and partial condensation to total condensation was 35.0 °C under relative humidity of 70%, 30.0 °C under relative humidity of 80%, respectively. Condensation improved the outlet primary air temperature, total heat transfer, water consumption rate and condensation rate but lowered the wb-effectiveness. Furthermore, the thermal resistance of condensate film was non-ignorable because of thick water film.